Transcriptomic signatures for human male infertility - Hodžić, Alenka; Maver, Aleš; Zorn, Branko; Petrovič, Daniel; Kunej, Tanja; Peterlin, Borut (Frontiers in Molecular Biosciences, 2023)
Introduction: Male infertility is a common, complex disorder. A better understanding of pathogenesis and etiology is needed for timely diagnosis and treatment. The aim of this study, therefore, was to identify genes involved in the pathogenesis of idiopathic male infertility based on data from transcriptomic level supported with data from genomic level. Materials and Methods: First, we performed whole gene expression analysis in 20 testis biopsy samples of patients with severely impaired (10) and normal spermatogenesis (10). Further, we have performed systematic review of comparable male infertility studies and overlapped the most significantly expressed genes identified in our study with the most differentially expressed genes from selected studies. Gene Ontology analysis and KEGG functional enrichment have been performed with Enrichr analysis tool. Additionally, we have overlapped these genes with the genes where rare variants have been identified previously. Results: In 10 patients with severely impaired spermatogenesis and 10 controls, we identified more than 1800 differentially expressed genes (p<0.001). With the systematic review of three previously performed microarray studies that have met inclusion criteria we identified 257 overlapped differentialy expressed genes (144 down-regulated and 113 up-regulated). Intersection of genes from transcriptomic studies with genes with identified rare variants revealed a total of 7 genes linked with male infertility phenotype (CYP11A1, CYP17A1, RSPH3, TSGA10, AKAP4, CCIN, NDNF). Conclusions: Our comprehensive study highlighted the role of four genes in pathogenesis of male infertility and provided supporting evidence for three promising candidate genes which dysfunction may result in a male infertility disorder.